Integrating metalloporphycenes into p-type NiO-based dye-sensitized solar cells - Feihl, Sebastian; Costa, Ruben D.; Brenner, Wolfgang; Margraf, Johannes; Casillas Pacheco, Ruben; Langmar, Oliver; Browa, Anne; Shubina, Tatyana; Jux, Norbert; Guldi, Dirk Michael; Clark, Timothy (Chemical Communications, 2014)
In the current work, we have explored a novel synthetic route towards metalated porphycenes and their use in p-type NiO-based dye-sensitized solar cells. Particular emphasis is placed on the influence that the relative positioning of the anchoring group exerts on the DSSC performance.